The Relationship Between Stock Returns and Economic Growth: Historical Patterns and Sectoral Dynamics - Mikkola, Jonni (My University, 2025)
This study investigates the relationship between stock market returns and GDP growth in the long run, and how other factors affect stock performance. Research examines the impact of different macroeconomic factors, such as inflation, monetary policy, and technological progress. US stocks and economy have outperformed European stocks and economic growth over a decade. To find the reason for this, the study investigates whether investors should primarily focus on growing economies to get better returns. Furthermore, it examines how different sectors respond to economic growth and whether sector performance can be an indicator of future economic expansion or stock market returns. Economic theories suggest that efficient stock market prices reflect available information and expected future profits, which can be affected by economic conditions such as GDP growth and financial stability. However, studies have shown that this relationship is quite complicated, with evidence showing that stock markets and economic growth have only a weak correlation. The main findings of this study are i) Higher economic growth has not led to higher stock returns. ii) The general market trend can be predicted by sensitive sectors. iii) Markets were found to efficiently price stocks under different market areas, preventing excess returns. Tämä tutkimus tarkastelee osaketuottojen riippuvuutta talouden kasvuun pitkällä aikavälillä sekä kuinka muut tekijät vaikuttavat osakkeiden tuottoihin. Tutkimus arvioi myös muiden makrotaloudellisten tekijöiden, kuten inflaation, rahapolitiikan ja teknologisen kehityksen vaikutusta toteutuneisiin tuottoihin. Yhdysvaltojen osakkeet ja talouskasvu ovat tehneet merkittävää ylituottoa Eurooppaan verrattuna yli vuosikymmenen ajan. Tämän syyn selvittämiseksi, tutkimuksessa tutkitaan näiden korrelaatiota ja pitäisikö sijoittajan keskittyä kasvaviin talousalueisiin saavuttaakseen paremmat tuotot sijoituksilleen. Lisäksi arvioidaan eri toimialojen reagointia taloussuhdanteeseen ja sitä, voiko sijoittaja hyödyntää sitä arvioidessaan osakkeiden ja talouden tulevaa trendiä. Talousteorioiden mukaan markkinat hinnoittelevat tehokkaasti kaiken avoimen informaation osakkeiden hintoihin, mihin voi vaikuttaa esimerkiksi talouden tila, kuten talouden kasvu ja vakaus. Aiempi kirjallisuus kuitenkin osoittaa, että osaketuottojen korrelaatio talouden kasvuun on ollut vähäinen. Tutkimuksen päälöydöksiä ovat: i) Korkea talouden kasvu ei ole johtanut parempiin osaketuottoihin. ii) Tulevaa markkinatrendiä voidaan ennustaa tutkimalla suhdanneherkkiä toimialoja. iii) Markkinat hinnoittelevat osakkeiden eri maantieteelliset kasvuoletukset tehokkaasti, estäen ylituoton saavuttamisen.
Keywords: talouskasvu; osakkeet; inflaatio; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|